2018
DOI: 10.1016/j.watres.2018.05.054
|View full text |Cite
|
Sign up to set email alerts
|

The role of zeta potential in the adhesion of E. coli to suspended intertidal sediments

Abstract: The extent of pathogen transport to and within aquatic systems depends heavily on whether the bacterial cells are freely suspended or in association with suspended particles. The surface charge of both bacterial cells and suspended particles affects cell-particle adhesion and subsequent transport and exposure pathways through settling and resuspension cycles. This study investigated the adhesion of Faecal Indicator Organisms (FIOs) to natural suspended intertidal sediments over the salinity gradient encountere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 57 publications
3
12
0
Order By: Relevance
“…The increased adhesion may partly be due to the plentiful binding sites provided by the remaining organic matter attached to or between sediment particles and therefore surfaces are more available for microbes to adhere. A similar mechanism has been reported in a previous study on the role of cell and particle characteristics in the adhesion of Escherichia coli bacteria to suspended intertidal sediments (Wyness et al, 2018). This work showed that all strains examined adhered more efficiently to organic sediments than other abiotic sediment (i.e.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The increased adhesion may partly be due to the plentiful binding sites provided by the remaining organic matter attached to or between sediment particles and therefore surfaces are more available for microbes to adhere. A similar mechanism has been reported in a previous study on the role of cell and particle characteristics in the adhesion of Escherichia coli bacteria to suspended intertidal sediments (Wyness et al, 2018). This work showed that all strains examined adhered more efficiently to organic sediments than other abiotic sediment (i.e.…”
Section: Discussionsupporting
confidence: 88%
“…The physical disturbance by hydrodynamic forces cannot remove all organic material in sedimentary systems, i.e. A similar mechanism has been reported in a previous study on the role of cell and particle characteristics in the adhesion of Escherichia coli bacteria to suspended intertidal sediments (Wyness et al, 2018). As a result, bio-aggregates are introduced when they enter a water column (Figure 9).…”
Section: Discussionsupporting
confidence: 74%
“…For smaller events (e.g. Event 3: <5.0 mm), the lack of response in E. coli concentration with increasing scale above the headwater catchments could be due to a lack of proximal, hydrologically connected sources, but also attenuation of E. coli by processes such as attachment to sediment particles and settling in stream bed sediments as the hydraulic gradient, and hence stream flow velocity, decreases (Schiperski et al., 2016; Wyness et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Zeta potential was calculated using the Smoluchowski model. Data acquisition from 15 events was recorded for every sample, and the average Zeta potential was determined from four replicates (56).…”
Section: Bacterial Cell Size and Zeta Potential Measurementsmentioning
confidence: 99%